FP-LAPW Study of the EFG at Impurity Sites in Oxides: Cd in Rutile TiO2 - Errico, Leonardo Antonio (2000)
We report here first-principles determination of the electric-field gradient (EFG) tensor at the Cd impurity located at cation sites in rutile TiO2. As far as we know, these represent the first ab initio calculations at impurity sites with the FP-LAPW method in oxide systems. We used super-cells to simulate the diluted impurity in the crystal. The free-relaxation process performed in our study shows that the changes in distances of the oxygen nearest-neighbours to the impurity are not isotropic as was supposed in a previous study within the muffin-tin approximation. Our prediction for the EFG component of major absolute value agrees well with the experiment and is opposite in sign and direction if isotropic relaxations are assumed. Our value of the asymmetry parameter η also compares very well with the experimental value.